(untitled) (Journal of Legal Studies, 2019)
Some aspects of the possibility of using euthanasia are covered. The author draws attention to the relation between the categories "euthanasia" and "bioethics". The emphasis has been placed on the legal and medical aspects of the applying of euthanasia, based on the practice of the Netherlands.